(untitled) (Fiep Bulletin - online, 2011)
The need to move long distances, people increasingly prioritize comfort, economy and security, which made the road one of the most important conventional volume of users. The immobility in a seated position, within the limitations of chair and the resulting positions of the passenger to take a room in search of comfort. We conducted this study with the aim of analyzing the discomfort caused by sitting posture in passengers during the bus trips. We used a closed questions questionnaire, application of the statement of seat discomfort and anthropometry in 78 subjects between 18 and 76 years, 47 women and 31 men, Station Road Vacaria-RS to Lages-SC. The result obtained through analysis of data showed discomfort during travel regions in the neck (20%), lumbosacral (45%) and limbs (35%). Although the dissatisfaction have been reported for the space of the legs (36%) and the backrest support (22%), which are the cause of discomfort. The dissatisfaction and discomfort of bus passengers interviewed was evident, emphasizing the need for ergonomic guidelines by a qualified professional such as physiotherapist.